Effectiveness of The Problem-based Learning Model Assisted with Ruangguru Application on Increasing Students' Mathematical Problem Solving Ability - Ariyani, Dewi; Setiaji, Heru Agni (Faculty of Tarbiya and Teacher Trainning, Universitas Islam Negeri Prof. K.H. Saifuddin Zuhri Purwokerto, 2024)
The aim of the research is to determine the effectiveness of the problem-based learning model with the help of Ruangguru application to improve students' mathematical problem-solving skills. This study is a quasi-experimental research ( quasy -experimental design) with a quantitative approach. The design of this study is Nonequivalent Control Group Design. The population in this study were students of grade VIII SMP Negeri 2 Ajibarang and the samples used were taken by simple random sampling technique and the sample results obtained were students of grade VIII A (as a control class) and grade VIII B (as an experimental class) a total of 64 students. The instrument used in this study is a description test consisting of pretest and posttest. The results of this study are the average value of the ability to solve mathematical problems of students who are subject to the problem-based learning model assisted Ruangguru application more than not subject to the learning model is seen from the independent samples t test with the results of significance 0.000 ≤0.05then there is a significant difference in mathematical problem-solving abilities of experimental and control class students. Ruangguru's problem-based learning model is effective to improve the ability to solve mathematical problems by obtaining the average n-gain test in the experimental class of 60.96% with a fairly effective interpretation and control class of 20%with in effective interpretation.